Isolation, identification, and antimicrobial activity of psychrophilic freshwater microalgae Monoraphidium sp. from Almaty region (International Journal of Biology and Chemistry, 2020)
Microalgae is one of the potential biotechnologically valuable groups of photosynthetic microorganisms and represent the most promising resource for new products and applications. In this study, our efforts were focused on identification, isolation, and characterization of psychrophilic microalgae from the underinvestigated extreme environment. Three new isolates were isolated from the frozen Big Almaty Lake, but only for one of them the attempt to clean from bacteria and fungus was successful and it was obtained in algologically and bacteriologically pure form. The taxonomy and phylogeny of the green microalgae, was examined based on morphological (light and scanning electron microscopy) and sequencebased approach using universal molecular markers of ITS region and rbcL gene. Morphological and molecular characterization showed that this green microalgae is Monoraphidium sp. (strain ZBD-06). The antibacterial activity of the isolate was determined as well and 60% methanol extract of Monoraphidium sp. was used for antibacterial activity by disk diffusion assay and minimum inhibitory concentration using eleven different types of pathogenic bacteria including Gram positive (Bacillus subtilis ATCC 6633, Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 12228) and Gram negative bacteria (Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 13883, Pseudomonas aeruginosa ATCC 27853, Proteus vulgaris ATCC 13315, Salmonella typhimurium ATCC 14028, Yersinia pseudotuberculosis ATCC 911, and Enterobacter cloacae ATCC 13047). The zone of inhibition (10±2 mm in diameter with 10ul of extract and 20±2 mm in diameter with 30uL) was observed against Klebsiella pneumoniae ATCC 13883.